Political participation of the Roma minority in Spain. Readjustment of legal mechanisms with a minority perspective - Jurado Cerrón, Doly Rocío (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
This article addresses how the political participation of its main ethnic minority, the roma population, has been managed in Spain. To this end, it begins with some notes on the right to political participation, the mechanisms of direct and indirect democracy and the access to these mechanisms by the majority population at the macro level and the case of the roma minority at the micro level. Within this framework, it studies the situation of historical and structural discrimination that is behind the underrepresentation or almost null access to decision-making spaces. Finally, it proposes as alternatives to this problem the creation of positive actions and, complementarily, a readjustment of legal mechanisms with a minority perspective, among which are: constitutional and electoral law reform, the creation of ad hoc parliamentary commissions, and associationism as an alternative for political incidence.